Using subdivision surfaces and PN triangles for game applications - Pu, Guannan (2010)
Polygonal meshes (in particular, triangular meshes) are commonly used to represent and render models and objects in game applications. Due to speed and storage limitation, usually only coarse meshes and simplified meshes are used for rendering. To generate more details from a coarse mesh, several techniques can be applied, like normal mapping, displacement mapping, subdivision surfaces and other techniques.